The efficacy and safety of alteplase treatment in patients with acute ischemic stroke with unknown time of onset: -Real world data-. (January 2023) - Terasawa, Yuka; Shimomura, Ryo; Sato, Kota; Himeno, Takahiro; Inoue, Tomoyuki; Kohriyama, Tatsuo
Highlights: We reported the frequency, the efficacy and safety of alteplase treatment in patients with acute ischemic stroke with unknown time of onset in a real-world clinical setting. We use DWI-FLAIR mismatch for patients' selection for alteplase treatment. Alteplase treatment was performed in 18% of patients with an unknown time of stroke onset. Our cohort was older than previous study, however, there were no significant differences in frequency of all hemorrhagic complications. Abstract: Introduction: Treatment with alteplase for acute ischemic stroke patients with an unknown time of onset is safe and effective. However, clinical trials have some selection bias. The purpose of this study was to clarify the efficacy and safety of alteplase treatment in patients with unknown time of onset in a real-world clinical setting. Methods: We included consecutive patients with acute ischemic stroke visited within 4.5 h of onset or symptom recognition. We divided patients into two groups: onset clear group (C-group) and unknown time of onset group (U-group). We treated patients with an unknown time of onset if the DWI-FLAIR mismatch was positive. We calculated the prevalence of alteplase treatment in each group and compared prognosis between the two groups. Results: Six hundred thirty-two patients arrived within 4.5 h of onset or symptom recognition. Of these, 446 patients (71 %) were in the C-group and 186 (29 %) in the U group. Alteplase treatment was performed in 35 % of patients in the C group and in 18 % in the U group (p < 0.001). Favorable outcomes at 90 days in patients treated with alteplase were comparable between the C group (52 %) and the U group (53 %) (p = 0.887). All hemorrhagic complications, including non-symptomatic hemorrhagic transformation, occurred in 11 of 157 patients (7 %) in the C-group and one of 34 patients (3 %) in the U-group (p = 0.696). Conclusion: In a real-world clinical setting, alteplase treatment was performed safe in 18% of patients with an unknown time of stroke onset based on patient selection using the DWI-FLAIR mismatch.